2013
DOI: 10.1021/ja408003d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Open-Shell, Bimetallic Mn/Fe Trinuclear Clusters

Abstract: Concomitant deprotonation and metallation of hexadentate ligand platform tbsLH6 (tbsLH6 = 1,3,5-C6H9(NHC6H4-o-NHSiMe2 tBu)3) with divalent transition metal starting materials Fe2(Mes)4 (Mes = mesityl) or Mn3(Mes)6 in the presence of tetrahydrofuran (THF) resulted in isolation of homotrinuclear complexes (tbsL)Fe3(THF) and (tbsL)Mn3(THF) respectively. In the absence of coordinating solvent (THF) the deprotonation and metallation exclusively afforded dinuclear complexes of the type (tbsLH2)M2 (M = Fe or Mn). The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 64 publications
0
30
0
1
Order By: Relevance
“…Metalation of tbs LH 6 with three equivalents of Cr(NTMS 2 ) 2 (thf) 2 (TMS=trimethylsilyl) at 120 °C yielded the trinuclear cluster ( tbs L)Cr 3 (thf) ( 1 , Figure ). At lower temperatures, metalation arrested at a dinuclear form similar to those previously reported on this platform . Crystals suitable for single‐crystal X‐ray diffraction (SC‐XRD) were grown from a concentrated diethyl ether solution of 1 at −35 °C.…”
Section: Figurementioning
confidence: 68%
“…Metalation of tbs LH 6 with three equivalents of Cr(NTMS 2 ) 2 (thf) 2 (TMS=trimethylsilyl) at 120 °C yielded the trinuclear cluster ( tbs L)Cr 3 (thf) ( 1 , Figure ). At lower temperatures, metalation arrested at a dinuclear form similar to those previously reported on this platform . Crystals suitable for single‐crystal X‐ray diffraction (SC‐XRD) were grown from a concentrated diethyl ether solution of 1 at −35 °C.…”
Section: Figurementioning
confidence: 68%
“…In the parent L5 , different redox states have been assigned by structural and spectroscopic techniques . Furthermore, pre‐organized ligand scaffolds comprising o ‐phenylene‐ N ‐alkyl‐ N ′‐(trialkylsilyl)amides have been used for the stabilization of homo‐ and hetero‐metallic 3d metal clusters …”
Section: Methodsmentioning
confidence: 99%
“…Applications span a variety of research areas in solid state chemistry [138,[228][229][230]564], including the discrimination of Zn and Ga in microporous materials [565] or of Pb and Bi in minerals [566], the investigation of the distribution of cations in multi-cationic zeolites [229,567,568], substitution of Cu by Fe, Co, Ni, and Zn in high-critical-temperature superconductor cuprates [556]. A few recent applications of contrast-mode anomalous X-ray diffraction specifically deal with the structural determination of coordination compounds, including multinuclear metal complexes [569][570][571] and MOFs [572]. A representative example is the study of Co−Co and Fe−Co bonds in a series of coordination complexes with formally mixed-valent [M2] 3+ cores (where M = Fe, Z= 26; Co, Z = 27), by Zall et al [570].…”
Section: Anomalous Xrd and Xrs In Coordination Chemistry: The Charm Omentioning
confidence: 99%
“…The refinement demonstrated that only a minor amount of metal-site mixing occurs in the heteronuclear complex: this compound is precisely described by the structure formula (Fe0.94(1)Co0.06(1))(Co0.95(1)Fe0.05(1))LPh, where L Ph = phenyl-substituted tris(amidinato)amine, as depicted by the pie charts in Figure 8a. [571]. Finally, a relevant example of the use of anomalous XRD in the structural characterization of MOFs is provided by Brozek et al [572].…”
Section: Anomalous Xrd and Xrs In Coordination Chemistry: The Charm Omentioning
confidence: 99%